Outline of a modified social impact bond to address the problem of youth employability in the tourism sector - Ponce Villegas, Albert Moises (2020)
The present essay focuses its development on the analysis of two important fields for our country: human capital and innovation. On the first, we emphasize the critical challenges facing the youth sector for its acquisition and development. Likewise, in terms of innovation, we ponder over some new public policy instruments that are being developed in other latitudes with positive results. Finally, we develop a proposal that tries to connect both points. That is, an instrument, the social impact bond, with proven results in other territories, projecting it and adapting it to a possible implementation in the youth population of the service sector, specifically in the tourism sector, around their first work experience. The formula is proposed at the scale level for prototyping, validation and obtaining lessons learned.